Sea water intrusion appraisal through ground water chemistry in coastal (Cuddalore) district of Tamilnadu, India - SHERENE, T.; BALASUBRAMANIAM, P.; KALEDHONKAR, M. J.; RAVIKUMAR, V (Journal of Soil and Water Conservation, 2020)
Coastal aquifers are increasingly threatened by seawater intrusion due to increased urbanization, groundwater exploitation, and global sea-level rise. This raises the need to transform the information under a GIS framework to define vulnerable areas prone to seawater intrusion. Ground water quality map of Cuddalore district was prepared and only 4 coastal blocks were studied for sea water intrusion which were located from seashore to 30 km inland distance. A hydrogeochemical investigation was conducted in these coastal blocks and around 52 nos. of ground water samples were collected to identify the influence of saltwater intrusion and suitability of groundwater for domestic and agricultural purposes. Among the 4 coastal blocks studied, only Parangipettai and Kumaratchi blocks were suspected for sea water intrusion. The ground water chemistry commonly found to be Mg-HCO3 type. However, NaCl is also the dominant water facies, bicarbonate and chloride ions were the dominant anions, whereas magnesium and sodium were the dominant cations. Regarding sea water intrusion, the high Mg/Ca ratio (> 5.4) may be indicative of sea water contamination in these locations. According to Cl /CO3 2- +HCO3 - ratio (> 6.6) the screened locations have highly contaminated ground water (near sea water). Based on Na/Cl ratio (<0.86) the contamination may be due to marine source of origin. Hence, construction of check dams in these areas across the rivers at frequent intervals will assist in mitigating the problems of sea water intrusion by increasing ground water recharge.